2020
DOI: 10.2147/rmhp.s269315
|View full text |Cite
|
Sign up to set email alerts
|

<p>Strategies to Prevent Healthcare-Associated Infections: A Narrative Overview</p>

Abstract: Healthcare-associated infections (HCAIs) are a major source of morbidity and mortality and are the second most prevalent cause of death. Furthermore, it has been reported that for every one-hundred patients admitted to hospital, seven patients in high-income economies and ten in emerging and low-income economies acquire at least one type of HCAI. Currently, almost all pathogenic microorganisms have developed antimicrobial resistance, and few new antimicrobials are being developed and brought to market. The lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 178 publications
(254 reference statements)
1
76
0
4
Order By: Relevance
“…Infection prevention and control, antimicrobial surveillance, and antimicrobial stewardship are believed to be the principal strategies for local, national, and international systems to prevent the development of AMR and reduce avoidable healthcare-associated infections (HCAIs). 79 , 243 , 254 Public health professionals advocate ways to reduce pointless prescriptions to evade the onslaught of AMR. This becomes evident when there are high levels of antimicrobial use among COVID-19 patients, highlighting the necessity to institute stewardship agendas.…”
Section: Professionals Annotationmentioning
confidence: 99%
“…Infection prevention and control, antimicrobial surveillance, and antimicrobial stewardship are believed to be the principal strategies for local, national, and international systems to prevent the development of AMR and reduce avoidable healthcare-associated infections (HCAIs). 79 , 243 , 254 Public health professionals advocate ways to reduce pointless prescriptions to evade the onslaught of AMR. This becomes evident when there are high levels of antimicrobial use among COVID-19 patients, highlighting the necessity to institute stewardship agendas.…”
Section: Professionals Annotationmentioning
confidence: 99%
“…It has been reported that for every one-hundred patients admitted to hospital, seven patients in high-income economies and ten in emerging and low-income economies acquire at least one type of HAI ( Haque et al, 2020 , Danasekaran et al, 2014 , Khan et al, 2017a , Khan et al, 2017b , Haque et al, 2018 , Klevens et al, 2007 , WHO, 2016 ). In the United States at any one time, 4 % of the hospitalized patients are affected by an HAI ( Magill et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of these infections in underdeveloped countries is about three times higher than in developed countries [ 3 ]. In these countries, this rate varies between 5.7–19.1% [ 4 ]. In Iran, most of these infections occur in intensive care units and surgical wards [ 5 ].…”
Section: Introductionmentioning
confidence: 99%